Mechanical properties influencing athlete-surface interaction on tennis court surfaces - Colino, E.; García-Unanue, J.; Felipe, J. L.; Quintana-Garcia-Milla, I. (Sports Engineering, 2024)
Tennis is a sport in which the surface plays an important role in performance and injury risk. Professional players face an extensive competition calendar in which they must adapt to different types of surfaces. However, unlike other sports, tennis lacks standards that regulate surface properties affecting athlete-surface interaction. The objective of this study was to mechanically evaluate shock absorption, vertical deformation, energy restitution and slip resistance in different types of tennis surfaces, compare them with each other and look for correlations between variables. Thirty-six tennis courts (12 hard court, 16 clay, 8 artificial grass) were evaluated. All variables differed significantly between surfaces (p < 0.001). Shock absorption (1.1 ± 0.5 to 13.9 ± 3.4%) and vertical deformation (0.02 ± 0.04 to 1.07 ± 0.19 mm) were lower on hard court compared to clay and artificial grass; energy restitution (72.5 ± 4.7 to 89.9 ± 1.5%) showed the opposite; and slip resistance (in Pendulum Test Value) was lower on clay (53.6 ± 2.5) compared to grass (61.4 ± 1.3) and hard court (66.6 ± 1.1). No significant correlations between variables were identified in hard court. However, both clay and artificial grass showed a significant positive correlation (p < 0.001) between shock absorption and vertical deformation (0.872 and 0.947, respectively), and a significant negative correlation (p < 0.001) between shock absorption and energy restitution (- 0.807 and - 0.981, respectively). Also, significant negative correlations were found between vertical deformation and energy restitution both in clay (- 0.802; p < 0.001) and artificial grass surfaces (- 0.890; p < 0.01). As for the shock absorption, only a significant negative correlation with vertical deformation in artificial grass (- 0.715; p < 0.05) was identified. This study contributes initial evidence for further research to inform future International Tennis Federation regulations aimed to assess and control the mechanical properties of tennis surfaces affecting athlete-surface interaction.